2007
DOI: 10.1002/pits.20255
|View full text |Cite
|
Sign up to set email alerts
|

Individualized education programs for youth with Autism Spectrum Disorders

Abstract: Children with Autism Spectrum Disorders (ASD) present with a broad array of deficits and excesses that require educational intervention. The Individualized Education Program (IEP) serves as the blueprint for educational intervention but it can sometimes be difficult to identify which goals and objectives should be addressed with this population. It is necessary to be familiar with the defining features of ASD and the associated characteristics that youth may demonstrate in order to develop appropriate educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 35 publications
0
25
0
3
Order By: Relevance
“…The majority of research on social skills interventions for individuals with ASD focuses on the development of specific social skills (such as initiating greetings, turn taking, making eye contact, smiling, or waving goodbye [Ozonoff 2002;Krasny 2003;Wilczynski 2007]) or one type of social relationship (such as social inclusion/membership [Kalyva and Avramidis 2005]). However, in examining the impact of a collaborative iPad game on social skills, we found that one technology can support multiple skills and relationships.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of research on social skills interventions for individuals with ASD focuses on the development of specific social skills (such as initiating greetings, turn taking, making eye contact, smiling, or waving goodbye [Ozonoff 2002;Krasny 2003;Wilczynski 2007]) or one type of social relationship (such as social inclusion/membership [Kalyva and Avramidis 2005]). However, in examining the impact of a collaborative iPad game on social skills, we found that one technology can support multiple skills and relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Designing IEPs, specific to individuals with ASD, the objectives, target behaviors, and levels of supports should all be clearly defined, specific, and developmentally appropriate (14). Specific IEP goals should be individualized, but reflective of common characteristics of autism, including communication goals related to requesting, labeling, identifying, following directions, making conversation, using spontaneous and generalized communication skills, greeting, and using and understanding non-verbal communication.…”
Section: A Special Focus On Asd In Educational Settingsmentioning
confidence: 99%
“…Specific IEP goals should be individualized, but reflective of common characteristics of autism, including communication goals related to requesting, labeling, identifying, following directions, making conversation, using spontaneous and generalized communication skills, greeting, and using and understanding non-verbal communication. Social interaction goals and objectives for an IEP could include joint attention and early social engagement skills, social play, pretend play, consideration of the perspective and feelings of others, friendship, social skills, and problem-solving (14). Lastly, goals and objectives related to restricted and repetitive behaviors could include managing and reducing or eliminating stereotypic behaviors, understanding and demonstrating flexibility, and managing and reducing obsessive thoughts and compulsive behaviors.…”
Section: A Special Focus On Asd In Educational Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Günlük yaşam becerileri alanında başlıca öğretimsel odaklar şunlar olabilir; tuvaletini yapma, kişisel hijyen, giyinme, yemek yeme, materyal hazırlama, düzenleme, görevi tamamlama, temizlik yapma, sağlığını koruma vb. (Wilczynski, Menusek, Hunter, & Mudgal, 2007).…”
Section: Günlük Yaşam Becerileriunclassified